2013
DOI: 10.1016/j.apmr.2012.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Community Participation, Supports, and Barriers of School-Age Children With and Without Disabilities

Abstract: Results provide insights about where greater efforts are needed to support community participation of school-age children with disabilities. Further study with a more diverse sample in terms of race/ethnicity, family income/education levels, and geographic region is needed to determine the extent to which results may be generalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
186
2
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(219 citation statements)
references
References 39 publications
23
186
2
8
Order By: Relevance
“…Considering these individuals often report decreased rates of social participation and employment (Bedell et al, 2013;Harris Interactive, 2010;Shattuck, Orsmond, Wagner, & Cooper, 2011), the potential benefits of mentoring could be particularly salient for this population. A few studies have examined the impact of peers with DD and showed these individuals were successful as peer tutors in promoting skill development (Bobroff & Sax, 2010;Hibbert, Kostinas, & Luiselli, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Considering these individuals often report decreased rates of social participation and employment (Bedell et al, 2013;Harris Interactive, 2010;Shattuck, Orsmond, Wagner, & Cooper, 2011), the potential benefits of mentoring could be particularly salient for this population. A few studies have examined the impact of peers with DD and showed these individuals were successful as peer tutors in promoting skill development (Bobroff & Sax, 2010;Hibbert, Kostinas, & Luiselli, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Recevoir davantage d'informations ressort particulièrement, que ce soit à propos de l'enfant (diagnostic, soutien éducatif) ou des ressources disponibles (Pelchat et al, 2008 ;Resch et al, 2010 ;Deris, 2012 ;Bedell et al, 2013). Tout autant citée, l'aide financière et matérielle s'avère nécessaire pour les familles (Dionne et al, 2006 ;Resch et al, 2010 ;Deris, 2012 ;Bedell et al, 2013). Dans l'étude de Resch et de ses collaborateurs (2010), les parents signalent notamment les difficultés à inclure leur enfant dans les systèmes éducatifs et sociaux ainsi que la diminution du soutien des proches avec les années.…”
Section: Des Familles En Situation De Mobilitéunclassified
“…Other environmental issues include accommodation strategies (e.g., ramps to enter buildings), treatment by therapists or educators, attitudes of educators, and, typically, developing relationships with peers in school settings. If unsupportive, these environmental factors can restrict children with disabilities from participating in everyday activities (Bedell et al, 2013). Such restrictions can also be a result of insufficient knowledge about pain management or how to cope with children with complex communication needs (Bornman & Donohue, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%